Pencak Dor in the Cyber World: An Analysis of Comments on Youtube - Sihombing, Lambok Hermanto; Harahap, Aris Masruri (Komunitas, 2019)
There has been a rise in the spread and new consumption of a traditional fighting sport from East Java, Indonesia. The sport is widely known as Pencak Dor. These days Pencak Dor has received internet users’ attention. People can easily find videos of Pencak Dor’s fights on the biggest video sharing site, YouTube. However, similar to what happens in the real world; various comments regarding the performance of Pencak Dor appear in the cyber world too. Using encoding-decoding concept from Stuart Hall, we try to unpack the complexity of the diverse comments appeared on YouTube regarding the practices. The result of this study suggested that topics appeared in the comments is not limited to the fight or the fighters. Interestingly, the topic is also about a debate and contestation between preserving the traditional sport and Islamic teachings. Having a root in Lirboyo Islamic Boarding School, Pencak Dor mixes violent culture and religious teachings. The diverse opinions that emerge on YouTube instead affirm that a code that an encoder sends is not necessarily decoded exactly the same as the encoder wants.